PA02.21. Stability study in ayurvedic products - Neeraj, PT (Medknow Publications & Media Pvt Ltd, 2013)
PURPOSE: The objective of stability study as per ICH is to provide evidence on how the quality of a drug substance or drug product varies with time under the influence of a variety of environmental factors such as temperature, humidity, and light, and to establish a retest period for the drug substance or a shelf life for the drug product and recommended storage conditions. Stability test is important not only in the process of product development, but also to assess the quality of existing products over a period of time. In the scenario of ayurveda, very little data is available regarding structured stability studies. It is also a tool to assess the life cycle of a product, and thereby derive its expiry period. It is an inevitable element in the documents related to the registration of ayurvedic products in other countries. When the ayurvedic products are subjected to stability studies, the dossier of an ayurvedic product becomes more scientific and acceptable. METHOD: Types of stability studies 1.Long–term studies : The long–term testing or real–time testing refer to conditions under which the product will remain stable for the specified period. 2. Accelerated studies : The accelerated testing conditions are at least 15 °C higher than the long–term study conditions and are intended to increase the rate at which degradation reactions take place thus revealing quality changes at an early stage Globally climatic zones are divided into 4 for stability study and the storage conditions for the climatic zones are as follows. for climate zones I and II Temperature Relative humidity Long–term studies 25 °C ??2 °C 60 % ??5 % Intermediate conditions 30 °C ??2 °C 65 % ??5 % Accelerated studies 40 °C ??2 °C 75 % ??5 % for climate zones III and IV Long–term studies 30 °C ??2 °C 65 % ??5 % Accelerated studies 40 °C ??2 °C 75 % ??5 % RESULT: A structured stability study enables to determine the shelf life of the product and thereby derive at its expiry period, most suitable storage and transport conditions. CONCLUSION: The paper provides a brief description on the requirement of stability testing, types of stability tests, the determination of transporting conditions based on stability data, the procedures and guide lines of stability study and the extrapolation of the generated data.